Interactive groups and the fulfillment of tasks in students from rural areas - Douglas José Giler Loor; José Alberto Vigueras Moreno (International Journal of Psychosocial Rehabilitation, 2020)
n the educational field, a problem that has plagued the normal development of institutions with a high incidence in rural areas, is the non-accompaniment of parents in curricular and extracurricular tasks of students, due to lack of time, disinterest, illiteracy, intra-family difficulties and little consolidation of knowledge by teachers. For this reason, the need arises to implement interactive groups within the classroom, to improve the fulfillment of tasks in rural students with the guidance of their representatives and teachers. In effect, the research was directed to qualitative methodology, the inductive-deductive method, bibliographic search and unstructured observation, who will give scientific rigor to the investigation, to demonstrate real situations based on the problems established in the academic process, at the In this regard, the results obtained reflect the non-compliance of the obligations of the students, analyzed from the cognitive, attitudinal, emotional and social factors, with the intention that teachers and education authorities know the difficult situation faced by a large number of children and their instead get parental involvement. The application of learning communities in schools is essential and thus improve the deficit of non-compliance, raising awareness among all the actors and thus contributing efforts as a team, having as a priority the ideal training of students; establishing what will be the best way to see this need overcome, where the support of all members of the educational community is evident.